Dating Strike‐Slip Ductile Shear Through Combined Zircon‐, Titanite‐ and Apatite U–Pb Geochronology Along the Southern Tan‐Lu Fault Zone, East China. Issue 4 (18th April 2023) - Qiu, Erkang; Zhang, Yueqiao; Larson, Kyle P.; Li, Bingxi
Abstract: Dating the timing of ductile shear deformation is critical to the understanding of complex, multi‐episode kinematics that commonly occur within the study of continental tectonics. The Tan‐Lu fault zone (TLFZ) in East China is a lithospheric discontinuity that records multistage sinistral strike‐slip shearing during Mesozoic time. Herein, based on field mapping, pressure‐temperature estimates via microstructures, quartz lattice preferred orientations, and geothermobarometer analysis, and U–Pb geochronology, we present a detailed examination of a portion of the southern TLFZ known as the Fucha Shan ductile shear zone. Two phases of sinistral ductile shear deformation in the shear zone are identified. The main phase occurred under amphibolite‐facies metamorphic conditions (500°C–650°C, 2.8–5.2 Kbar). U–Pb dating of synkinematic titanite indicate deformation occurred ca. 142–140 Ma. This age information is consistent with U–Pb dating of zircon from crosscutting granitic dikes that provide an upper limit of the shearing of ca. 134 Ma. A later, but less well‐developed phase of sinistral ductile shearing variably overprints older structures within the Fucha Shan shear zone at greenschist‐facies metamorphic conditions. U–Pb dating of apatite grains in rocks that record this later event are interpreted to indicate that shearing occurred ca. 118–108 Ma. These results provide new insight into Early Cretaceous shear deformation history within the southern TLFZ in the context of the late Mesozoic intracontinental deformation in East Asia. Plain Language Summary: The Tan‐Lu fault zone (TLFZ) is a large‐scale left‐lateral strike‐slip fault zone comparable to the San Andreas Fault in the western United States. It transects the eastern margin of the East Asian continent along a NNE striking array of structures. Movement along the TLFZ has been attributed to the Triassic collision between the North and South China Blocks, resulting in sinistral offset two high‐to‐ultra high pressure metamorphic belts, the Dabie in the west and the Sulu in the east. The fault zone, however, has been reactivated episodically during late Mesozoic intracontinental orogenesis in East Asia. In the present work, we present the results of detailed field mapping, microstructural characterization, quartz lattice preferred orientations, geothermobarometer analyses, and a combination of zircon, titanite and apatite U–Pb geochronology to date syn‐ to post‐shearing ductile deformation of the Fucha Shan shear zone in the southern TLFZ. We document two phases of sinistral strike‐slip shearing. Early deformation occurred at ca. 142–140 Ma under amphibolite‐facies metamorphic conditions, dated through analysis of synkinematic titanite U–Pb geochronology. Subsequent deformation occurred ca. 118–108 Ma at greenschist‐facies condition and was dated with apatite U–Pb geochronology. These geological results provide new insights into the pattern and kinematics of late Mesozoic intracontinental deformation in East Asia. Key Points: Two phases of sinistral ductile shearing are documented along the Fucha Shan shear zone of the southern Tan‐Lu fault zone The main phase occurred ca. 142–140 Ma under amphibolite‐facies conditions, dated with synkinematic titanite U–Pb geochronology The late phase occurred ca. 118–108 Ma under greenschist‐facies, dated through apatite U–Pb geochronology